2022
DOI: 10.1073/pnas.2210783119
|View full text |Cite
|
Sign up to set email alerts
|

Activity in a prefrontal-periaqueductal gray circuit overcomes behavioral and endocrine features of the passive coping stress response

Abstract: The question of how the brain links behavioral and biological features of defensive responses has remained elusive. The importance of this problem is underscored by the observation that behavioral passivity in stress coping is associated with elevations in glucocorticoid hormones, and each may carry risks for susceptibility to a host of stress-related diseases. Past work implicates the medial prefrontal cortex (mPFC) in the top-down regulation of stress-related behaviors; however, it is unknown whether such ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
4

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 131 publications
0
3
0
4
Order By: Relevance
“…PAG is one of the major centers of the descending pain inhibitory system, but it also projects rostrally to limbic midbrain structures including the VTA. , Activation of PAG has also been involved in stress resilience . In our study, the statistical analysis between naïve and PSNL showed significant differences in DAT ( P = 0.0252), Th ( P = 0.0424), BDNF ( P = 0.0084), μ opioid receptor ( P = 0.0004), and σ 1 R ( P = 0.0252) mRNA in the PAG (Figure ).…”
Section: Resultsmentioning
confidence: 48%
“…PAG is one of the major centers of the descending pain inhibitory system, but it also projects rostrally to limbic midbrain structures including the VTA. , Activation of PAG has also been involved in stress resilience . In our study, the statistical analysis between naïve and PSNL showed significant differences in DAT ( P = 0.0252), Th ( P = 0.0424), BDNF ( P = 0.0084), μ opioid receptor ( P = 0.0004), and σ 1 R ( P = 0.0252) mRNA in the PAG (Figure ).…”
Section: Resultsmentioning
confidence: 48%
“…Однако, несмотря на неспецифичность реакций организма на стрессогенное воздействие, в современной литературе уделяется большое внимание индивидуальнотипологическим особенностям реакций организма в условиях стресса, как личностным, психологическим [3], так и физиологическим и биохимическим, происходящим на разных уровнях функционирования организма, тканевом, клеточном, молекулярном [2,4]. При этом, учитывая современный уровень развития научных технологий, механизмы стресса сейчас изучаются на более глубоких уровнях структурно-функциональной организации организмаклеточном, молекулярном, что позволяет наиболее глубоко раскрывать процессы, вызванные стрессогенными факторами [5].…”
Section: материалы и методы исследованияunclassified
“…Однако САС находится в тесной взаимосвязи с другими гормональными системами организма, поэтому стресс -это генерализованная реакция организма [7]. САС входит вместе с гипоталамо-гипофизарно-надпочечниковой системой (ГГНС) в комплекс систем, объединенных в понятие «стресс-системы», активирующей и координирующей изменения при адаптивной реакции [4,5].…”
Section: материалы и методы исследованияunclassified
See 2 more Smart Citations